The Free World» - «The Old Land»: «The child» heritage of the Ukrainian Diaspora writers of Canada and the USA (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with Ukrainian Diaspora Literature for children and youth of American and Canadian centers in terms of “the native” and “the alien”concepts. The Ukrainian Diaspora in Canada and the United States is considered to be the widest one. It has also played a leading role in the formation and development of the Ukrainian literature for children and youth abroad. It is represented by more than fifty writers. At the same time, the Ukrainian literature for children and youth of the American and Canadian centers has its own peculiarities. Above all it includes the reality, which reflects the way how the Ukrainian exiles have to root being abroad far away from Ukraine over the ocean.The American and Canadian Diaspora writers represent in their works both the threats of and the possibilities of “the alien”, which arise in particular the problems of freedom and slavery, assimilation, biculturalism, care and self-esteem. Therefore, the works clearly show the implementation of two basic concepts: “The Free World” – “The Old Land”. In the Ukrainian foreign context, the positive aspect of the alien topos is the personification of Canada and the United States showing the image of a “cleared homeland”, with which the artists link the idea of “the Free World”. The works of the Diaspora writers contain the universal models of the Ukrainian community, designed to preserve the national identity in a foreign environment.At the same time, literature and critique for children raises the problem of denationalization and assimilation of Ukrainian children and youth. The Ukrainian Diaspora writers connect the image of the “The Old Land” with the problem of finding their own roots. It has determined the family theme in the works of the Canadian and American Diaspora writers. They often use in their works the set Ukrainian images such as ”father’s house”, “motherland”, “community”, “land”, “village”.In this way, through “the alien” concept and the culture of Canada and America with their rights and opportunities of the freedom of speech, the writers try to reach “the native”, considering in the works for children and youth the problems of national identity under new circumstances, such as: “How to be a Ukrainian child born away from the ethnic homeland?”. The works form two roles of Ukrainian youth: assimilate and bicultural.Thus, Diaspora writers combine in their works for children and youth two cultural worlds – the Canadian-American and Ukrainian ones. On the one hand, the realities of foreign countries are represented, and on the other hand, the mental image of Ukraine is presented. Consequently, the thematic searches of Ukrainian writers in Canada and the United States cover the problems of Ukrainian grouping in a foreign country, individual splitting under the influence of assimilation, the family and tradition continuity, serving Ukraine.
Keywords: the alien – the native; literature for children; Ukrainian Diaspora; bicultural; assimilation